Conserving Delhi's Pahari: Rethinking the Ridge as an Urban Cultural Landscape - Sharma, Jyoti Pandey (Indian Forester, 2017)
The geographical entity called the Delhi Region, home to the many capital cities of Delhi through the ages, is a triangular area marked by the river Yamuna and the Ridge, locally called Pahari, an extended spur of the Aravalli mountain ranges running in the south-eastern and north-western direction to complete the triangle formation. The Ridge, an important marker in the landscape of the cities of Delhi, besides serving as an urban forest, offered sites for dynastic capitals. Its utilitarianism as a built environment aerator notwithstanding, the ridge evolved as a cultural landscape with human interventions of varied socio-cultural dispensations, coexisting with the natural environment. While the significance of the Delhi Ridge as a natural landscape is underscored by the state and citizenry in equal measure in contemporary times, its reading and appreciation as a cultural landscape has been ignored. This Paper aims to address this gap by focussing on the ridge as a cultural product where nature and human interventions came together to produce a multilayered heterogenous landscape with tangible, utilitarian functions overlaid with abstract and experiential dimensions. It asserts that Delhi's Pahari is a worthy candidate for conservation not simply as an urban forest but as a cultural asset in its entirety.